High resolution-1Н NMR spectroscopy of oral liquid in young patients with wedge-shaped lesions - A. V. Mitronin; E. A. Srebnaya; V. I. Privalov; A. A. Prokopov (Эндодонтия Today)
Aim. The comparison of saliva 1Н NMR spectra in patients with wedge-shaped lesions before and after treatment.Materials and methods. Saliva as a study material was taken from patients with wedge-shaped lesions before and after treatment. The treatment method was remineralizing therapy that included the use of the oral rinse containing zinchydroxyapatite. 1Н NMR spectroscopy was chosen as an investigation method.Results. In most cases it is noted that after treatment the content of propionic and butyric acids was on the rise in relation of acetic acid. Overall concentration of 1Н protons didn't change significantly.Conclusions. 1Н NMR spectra analysis shows organic acid distribution in oral liquid before and after treatment, which helps to evaluate its response.